Assessment of Thyroid Hormones and Vitamin D Levels in Patients with Hereditary Hemoglobinopathies - Ghfran A. Kadim; Shrouk A. Hassan Al. Ibraheem (University of Thi-Qar Journal of Science, 2023)
Background: Hemoglobinopathies are ultimately developed many complications with a high of morbidity, secondary to iron overload. Thyroid dysfunction and bone disorders are the most common clinical manifestations. Methods: A case control study that included (140) patients with hemoglobinopathies and (50) healthy participants as a control. Anthropometric and biochemical measurements were estimated for all participants by standard methods. Results: This study were shown no significant differences (p > 0.05) for vitamin D, calcium, parathyroid hormone (PTH), thyroid stimulating hormone (TSH), free triiodothyronine (FT3) and free thyroid hormone (FT4). On other hand, showed significant (p <0.05) increase levels of phosphorus and ferritin in patient